Delayed presentation of iatrogenic esophageal perforation in children: A case series - Nangue Ngansob Loïs Landry; Meera Luthra; Aniruddh Setya (Journal of Pediatric Surgery Case Reports)
Introduction: Esophageal perforation is a rare condition in children. It can be fatal and its mortality increases if the diagnosis is delayed. Cases presentation: We report three pediatric cases of delayed presentation of esophageal perforation, all linked to an iatrogenic cause. Case 1 was a 3-year-old female child who had tachycardia, tachypnea and subcutaneous emphysema two days following a diagnostic endoscopy. She underwent an esophagram that showed a major leak in the mid esophagus. We placed a chest tube and did a surgical jejunostomy for enteral feedings. The perforation healed completely and spontaneously by day 23 of admission, as confirmed by a contrast study. Case 2 was an 11-year-old boy who had chest pain, dyspnea, fever, mild abdominal tenderness, and subcutaneous emphysema three days after undergoing an unsuccessful endoscopy to retrieve swallowed foreign bodies (2 coins). A barium swallow revealed a major leak in the lower third of the esophagus and plain chest fluoroscopy showed the coins in the pleural space. We did a thoracotomy, pleural wash-out, retrieval of the foreign bodies, and left a chest tube in place. The patient required an exploratory laparotomy and repair of a duodenal perforation of unknown etiology. At that time, we also did a gastrostomy and a jejunostomy. The perforation healed spontaneously, with a tiny leak remaining by day 50. Case 3 was a 4-year-old boy who developed a perforation of the lower third of the esophagus following an endoscopic balloon dilatation of an esophageal stricture. We placed a chest tube and did a gastrostomy and a feeding jejunostomy. The esophageal perforation had closed spontaneously by day 55. The three patients survived and still have their native esophagus. Conclusion: Esophageal perforations that present beyond the first 24 hours may be managed with conservative measurements, without a surgical esophageal repair.